Modified frailty index predicts postoperative outcomes in older gastrointestinal cancer patients. Issue 8 (24th April 2017) - Vermillion, Sarah A.; Hsu, Fang‐Chi; Dorrell, Robert D.; Shen, Perry; Clark, Clancy J.
Abstract : Background and Objectives: Frailty disproportionately impacts older patients with gastrointestinal cancer, rendering them at increased risk for poor outcomes. A frailty index may aid in preoperative risk stratification. We hypothesized that high modified frailty index (mFI) scores are associated with adverse outcomes after tumor resection in older, gastrointestinal cancer patients. Methods: Patients (60‐90 years old) who underwent gastrointestinal tumor resection were identified in the 2005‐2012 NSQIP Participant Use File. mFI was defined by 11 previously described, preoperative variables. Frailty was defined by an mFI score >0.27. The postoperative course was evaluated using univariate and multivariate analysis. Results: 41 455 patients (mean age 72.4 years, 47.4% female) were identified. The most prevalent form of cancer was colorectal (69.3%, n  = 28 708) and 2.8% of patients were frail ( n  = 1, 164). Frail patients were significantly more likely to have increased length of stay (11.7 vs 9.0 days), major complications (29.1% vs 17.9%), and 30‐day mortality (5.6% vs 2.5%), (all P  < 0.001). Multivariate analysis identified mFI as an independent predictor of major complications (OR 1.52, 95%CI 1.39‐1.65, P  < 0.001) and 30‐day mortality (OR 1.48, 95%CI 1.24‐1.75, P  < 0.001). Conclusions: mFI was associated with the incidence of postoperative complications and mortality in older surgical patients with gastrointestinal cancer.